Prevalence, Virulence Genes, Antimicrobial Susceptibility, and Genetic Diversity of Staphylococcus aureus from Retail Aquatic Products in China - Rong, Dongli; Wu, Qingping; Xu, Mingfang; Zhang, Jumei; Yu, Shubo (Frontiers in Microbiology, 2017)
Staphylococcus aureus is an important food-borne opportunistic pathogen that frequently causes severe blood and tissue infections or even fatal illnesses. Although S. aureus has been extensively studied in livestock and poultry foods in China, limited information has been reported in aquatic products. Accordingly, in this study, we aimed to characterize S. aureus in aquatic products purchased from retail markets in China. In total, 320 aquatic food samples were collected from 32 provincial capitals in China. The results showed that 119 samples (37.2%, 119/320) were positive for S. aureus by both qualitative and quantitative analyses. The contamination levels of 78.2% of samples ranged from 0.3 to 10 MPN/g, and six samples exceeded 110 MPN/g. A total of 119 S. aureus isolates from positive samples were selected to evaluate virulence factors, antibiotic resistance, and molecular characteristics. All S. aureus isolates were evaluated for the presence of 11 virulence genes by multiplex polymerase chain reaction, and α-hemolysin (hlα, 84.9%), fibronectin-binding protein A (fnbA, 79.0%), S. aureus enterotoxin E (see, 53.8%), and Panton-Valentine leucocidin (pvl, 50.4%) were identified as the major genes. These genes formed 56 different profiles, with the major profile identified as pvl-hlα-fnbA (28.6%). The antimicrobial susceptibility of all isolates was analyzed through the disk diffusion method, and the results showed high resistance to β-lactams, macrolides and tetracyclines, but susceptibility to linezolid and vancomycin. In addition, 26 sequence types (STs) were obtained via multilocus sequence typing (MLST), including seven novel STs, among which ST1 (20.2%), ST15 (18.5%), and ST188 (13.4%) were the most common STs. All the isolates were mecC negative, but nine isolates carrying mecA were evaluated by staphylococcal cassette chromosome mec (SCCmec) typing, all of which were SCCmecIII or SCCmecIV types. Isolates of SCCmecIII showed a high prevalence and were multidrug resistant. Our results showed that aquatic products could be a vehicle for transmission of virulence genes and multidrug-resistant S. aureus, representing a potential public health risk. The STs identified in this study indicated the genetic diversity of S. aureus, thereby providing important basic data for the dissemination of S. aureus in aquatic products.